2016
DOI: 10.1590/bjpt-rbf.2014.0164
|View full text |Cite
|
Sign up to set email alerts
|

Effects of non-invasive ventilation and posture on chest wall volumes and motion in patients with amyotrophic lateral sclerosis: a case series

Abstract: BackgroundThe effects of non-invasive ventilation (NIV) on the breathing pattern and thoracoabdominal motion of patients with amyotrophic lateral sclerosis (ALS) are unknown.Objectives1) To analyze the influence of NIV on chest wall volumes and motion assessed by optoelectronic plethysmography in ALS patients and 2) to compare these parameters in the supine and sitting positions to those of healthy individuals (without NIV).MethodNine ALS patients were evaluated in the supine position using NIV. In addition, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
12

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 28 publications
0
5
0
12
Order By: Relevance
“…The V RCa% was also reduced with trunk horizontalization, except in the change from the inclined posture to supine. Priori et al 8 and Magalhães et al 34 also observed a significant reduction of this variable in healthy individuals, when comparing the sitting position with the supine. However, in these studies, the authors evaluated the responses between supine and seated positions only, thereby preventing a comparison with the results obtained in the present study regarding inclined positions.…”
Section: Discussionmentioning
confidence: 85%
“…The V RCa% was also reduced with trunk horizontalization, except in the change from the inclined posture to supine. Priori et al 8 and Magalhães et al 34 also observed a significant reduction of this variable in healthy individuals, when comparing the sitting position with the supine. However, in these studies, the authors evaluated the responses between supine and seated positions only, thereby preventing a comparison with the results obtained in the present study regarding inclined positions.…”
Section: Discussionmentioning
confidence: 85%
“…Furthermore, in the sub-group with a premotor potential, there are parallel reductions in respiratory discomfort and premotor potential incidence during non-invasive ventilation ( Georges et al, 2016 ). Although from a separate cohort of ALS patients, non-invasive ventilation typically increases tidal volume ( Magalhaes et al, 2016 ), which suggests the reduction in premotor potential observed by Georges et al (2016) was not associated with decreases in ventilation (and the associated reduction in respiratory afferent feedback). Impaired automatic drive to breathe in CCHS is associated with a 100% incidence of premotor potentials to maintain ventilation during resting breathing in wakefulness ( Tremoureux et al, 2014a ).…”
Section: Discussionmentioning
confidence: 99%
“…Among these, 8 were retrospective studies [27][28][29][30][31][32][33][34] and 18 were prospective studies 24,[35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51] (Table 1). Six studies had control groups, 24,38,39,42,48,49 and only one study was a randomized controlled trial (RCT). 42 The population size in these studies varied from 5 to 140 patients.…”
Section: Resultsmentioning
confidence: 99%
“…Significant difference between cough peak flow, manually assisted cough peak flow, and manually assisted cough peak flow in NIV tolerant (p < 0.001) more efficient use of these muscles and possibly explaining the increase in lung volumes. 49 Although their findings were limited to ALS patients without significant bulbar impairment, they provide insight into how NIV helps with respiratory function. Another possible explanation for NIV's beneficial effects is that it may be improving central respiratory drive and lung compliance.…”
Section: Survivalmentioning
confidence: 99%